Pengelolaan Limbah Industri Pengolahan Hasil Perikanan: Studi Kasus Pada Usaha Mikro Kecil dan Menengah (UMKM) Sambal Ikan Tuna Di Kabupaten Cilacap - Mardiyana mardiyana; Any Kurniawati; Fadillah Fadillah; Murni Handayani (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2022)
One of the fisheries and marine potentials in Cilacap Regency is tuna fisheries. Catch tuna that landed at the Cilacap Ocean Fishery Port (PPSC) is high. Based on the analysis of the needs of actors in the tuna fisheries system in Cilacap, one of the components included in the system is the tuna fish processing industry. This is because there is only one tuna fishing company in Cilacap in 2009. The existence of these problems causes an increase in the growth of the micro-industry in the tuna fish processing business in Cilacap. This increase certainly has an impact on increasing the waste generated. This study aims to identify the type of waste generated and the waste management efforts of micro-industry players (MSMEs) processing tuna chili sauce in Cilacap and analyze the appropriate management design to be applied in the tuna fish sauce processing industry. The research data collection method was carried out by direct observation by conducting interviews with the owners of MSMEs. The results of field observations on MSMEs that produce tuna fish sauce produce organic and non-organic waste and the waste is simply thrown into the environment without any treatment first. Efforts to manage waste produced by MSMEs with tuna sauce have not yet been carried out due to limited human resources in knowledge about waste management. Based on the characteristics of the waste produced, several types of designs can be carried out by MSMEs, namely the management of organic and non-organic wastes to minimize the waste generated both in terms of quality and quantity as not to pollute the environment.